Peptic perforation in paediatric case of dengue: rare presentation - Pillai, Mahalaxmi; Rao, Gyaneshwar (International Surgery Journal, 2019)
Dengue fever is a common disease in tropical and subtropical regions and is characterized by fever, headache, and joint and muscle pain. Occasionally, patients develop abdominal and gastrointestinal symptoms. Gastrointestinal manifestations are increasingly being identified in severe dengue infection. Gastric perforation is very rare manifestation in dengue infection. Here we report a case of a 12 year old female who was diagnosed with dengue fever with perforative peritonitis due to prepyloric perforation with no prior symptoms of gastric ulcer.